The Effect of Company Growth, Capital Structure, Good Corporate Governance Mechanism, On Firm Value with Earnings Management as An Intervening Variable - Nawawi, Muhammad Ali (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: The aim of this research is to assess the effect of earnings management as an intervening variable on the value of main consumer goods sector businesses listed on the IDX between the years 2020 and 2022. Furthermore included in this assessment will be firm development, capital structure, and good corporate governance. Design: Using intentional sampling, this paper employs partial least squares (PLS) data analysis and hypothesis testing. The following describes the approach of this research. Finding: The results show that capital structure has no effect on earnings management; nonetheless, the growth of a firm increases its value and reduces the number of strategies for earning management. Moreover, good corporate governance increases the value of the firm and reduces the quantity of profits control done. Research Limitations: The results of this research are only relevant to companies listed on the IDX in the major consumer products industrial sector between the years 2020 and 2022 since of the limits of the research. These results might not be relevant for other sectors or historical eras. Practical Implications: Establishing efficient corporate governance policies is therefore crucial for investors and other stakeholders if they are to raise the value of the firm by reducing profits management techniques. This is so because the financial decisions other stakeholders and investors make depend on this. Originality/Value: This study offers fresh ideas on how corporate governance, capital structure, and firm size influence business value. Main consumer goods companies listed on the IDX employ earnings management as an intervening variable. This study stresses originality and worth as well.